Circumcision With Plastic Clamb in Newborn Infants - Yusuf Atakan Baltrak (Tropical Health and Medical Research, 2019)
Various devices were used to carry circumcision operation out. It noted that these devices, especially the Plastic Clamp method, significantly decrease complications as long as basic surgical rules, are followed. This study aims to examine the application of Plastic Clamp circumcision in infants. Children whose physical examinations revealed circumcision contradictions excluded from the study. During the study period, a total of 485 children was circumcised using the plastic clamp method under sedated anesthesia and by a single pediatric surgeon. Measurements take before operations and plastic clamps with diameters ranging from 1.2 to 1.6 cm used. The duration of the surgical procedure, early and late period post-operative complications, the separation duration of the plastic clamp, and problems evaluated. Study Results, the average length of the surgical operation was determined to be 5.5 minutes. The average hospital stay duration of the patients was 2 hours. During the follow-ups, edemas were observed in mucosal areas of 24 (4.9%) patients, 48 hours after the clamp placed and edema and swelling recovered seven days after the circumcision at the latest. On average, it observed that plastic clamp separated on its own in 7.1 days. It noted that in 4 (0.8%) patients, the plastic clamp separated prematurely during 6 hours following the operation due to pulling. Conclusion study plastic Clamp (Alisklamp) is starting to gain popularity because it falls off on its own and that it can be applied quickly under local anesthesia